Cost-effectiveness of the Perioperative Pain Management Bundle a registry-based study - Bojic, Suzana; Ladjevic, Nebojsa; Palibrk, Ivan; Soldatovic, Ivan; Likic-Ladjevic, Ivana; Meissner, Winfried; Zaslansky, Ruth; Stamer, Ulrike M; Baumbach, Philipp; Stamenkovic, Dusica (Frontiers in Public Health, 2023)
Introduction: The Perioperative Pain Management Bundle was introduced in 10 Serbian PAIN OUT network hospitals to improve the quality of postoperative pain management. The Bundle consists of 4 elements: informing patients about postoperative pain treatment options; administering a full daily dose of 1-2 non-opioid analgesics; administering regional blocks and/or surgical wound infiltration; and assessing pain after surgery. In this study, we aimed to assess the cost-effectiveness of the Bundle during the initial 24 hours after surgery. Materials and Methods: The assessment of cost-effectiveness was carried out by comparing patients before and after Bundle implementation and by comparing patients who received all Bundle elements to those with no Bundle element. Costs of postoperative pain management included costs of the analgesic medications, costs of labour for administering these medications, and related disposable materials. A multidimensional Pain Composite Score (PCS), the effectiveness measurement, was obtained by averaging variables from the International Pain Outcomes questionnaire evaluating pain intensity, interference of pain with activities and emotions, and side effects of analgesic medications. The incremental cost-effectiveness ratio (ICER) was calculated as the incremental change in costs divided by the incremental change in PCS and plotted on the cost-effectiveness plane along with the economic preference analysis. Results: The ICER value calculated when comparing patients before and after bundle implementation was 181.89 RSD (1.55 EUR) with plotted ICERs located in the northeast and southeast quadrants of the cost-effectiveness plane. However, when comparing patients with no bundle elements and those with all four bundle elements, the calculated ICER was -800.63 RSD (-6.82 EUR) with plotted ICERs located in the southeast quadrant of the cost-effectiveness plane. ICER values differ across surgical disciplines. Conclusions: The proposed perioperative pain management bundle is cost-effective. The cost-effectiveness varies depending on the number of implemented bundle elements and fluctuates across surgical disciplines.